Layered Crystalline and Amorphous Platinum Disulfide (PtS2): Contrasting Electrochemistry. Issue 30 (7th May 2019) - Wang, Yong; Szokolova, Katerina; Nasir, Muhammad Zafir Mohamad; Sofer, Zdenek; Pumera, Martin
Abstract: Group 6 transition metal dichalcogenides (TMDs), such as MoS2 and WS2 have been extensively studied for various applications while few studies have delved into other TMDs such as platinum dichalcogenides. In this work, layered crystalline and amorphous platinum disulfide (PtS2 ) were synthesized, characterised and their fundamental electrochemical properties were investigated. Both materials exhibited inherent oxidation and reduction reactions which would limit their operating potential window for sensing applications. Amorphous phase materials are considered to be promising electrocatalysts due to the porous, and nanostructured morphology with high concentration of unsaturated active sites. The electrocatalytic performances towards oxygen reduction (ORR) and hydrogen evolution reactions (HER) of crystalline and amorphous PtS2 were analysed. Amorphous PtS2 was found to exhibit superior electrocatalytic performances towards ORR and HER as compared to crystalline PtS2 . For HER, amorphous and crystalline PtS2 have overpotential values of 0.30 V and 0.70 V (vs. RHE) at current density of 10 mA cm −2, respectively. The influence of electrochemical reduction pre‐treatment on their catalytic behaviours was also investigated. Electrochemical reduction pre‐treatment on both crystalline and amorphous PtS2 removed the oxidized sulfate groups and increased the proportion of Pt 0 oxidation state which exposed more catalytic sites. As such, these materials were activated and displayed improved ORR and HER performances. Electrochemically reduced amorphous PtS2 outperformed the untreated counterparts and exhibited the best HER performance with overpotential of 0.17 V (vs. RHE) at current density of −10 mA cm −2 . These findings provide insights into the electrochemical properties of noble metal PtS2 in both crystalline and amorphous states which can be activated by electrochemical reduction pre‐treatment. Abstract : Two hit wonder : Layered crystalline and amorphous platinum disulfide (PtS2 ) were synthesized and their electrochemical and electrocatalytic properties were investigated. Both PtS2 materials were activated for hydrogen generation upon electrochemical reduction pre‐treatment.